rTMS Regulates the Balance Between Proliferation and Apoptosis of Spinal Cord Derived Neural Stem/Progenitor Cells - Zhao, Chen-Guang; Qin, Jie; Sun, Wei; Ju, Fen; Zhao, Yong-Lin; Wang, Rui; Sun, Xiao-Long; Mou, Xiang; Yuan, Hua (Frontiers in Cellular Neuroscience, 2020)
Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive technique that uses electromagnetic fields to stimulate brain. rTMS can restore impaired central nervous system and promote proliferation of neural stem/progenitor cells (NSPCs), but optimal stimulus parameters and mechanisms underlying these effects remain elusive. The purpose of this study is to investigate the effect of different rTMS stimulus parameters on proliferation and apoptosis of spinal cord-derived NSPCs, the expression of brain-derived neurotrophic factor (BDNF) after rTMS and the potentially underlying pathways. NSPCs were isolated from mice spinal cord and stimulated by different frequencies (1/10/20 Hz), intensities (0.87/1.24/1.58 T) and number of pulses (400/800/1500/3000) once a day for 5 consecutive days. NSPCs proliferation was analyzed by measuring neurosphere diameter and Brdu staining, apoptosis was detected by cell death enzyme-linked immunosorbent assay (ELISA) and flow cytometry, and NSPCs viability was assessed by cell counting kit-8 assay. We found that specific parameters of frequency (1/10/20 Hz), intensity (1.24/1.58T) and number of pulses (800/1500/3000) promote proliferation and apoptosis (p<0.05 for all), but 20 Hz, 1.58 T and 1500 pulses achieved the optimal response for the NSPCs viability. In addition, rTMS significantly promoted the expression of BDNF at mRNA and protein level, also increasing Akt phosphorylation (Thr308 and Ser473) (p<0.05). Overall, we identified the most appropriate rTMS parameters for further studies on NSPCs in vitro and in vivo. Furthermore, the effect of magnetic stimulation on NSPCs proliferation might be correlated to BDNF/Akt signaling pathway.